2007
DOI: 10.1080/00150190701509199
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stimulated Current (TSC) Studies on Resistance Degradation of Ni-MLCC

Abstract: To avoid the influence of spontaneous polarization, thermally stimulated current (TSC) measurements of BaTiO 3 -based multilayer ceramic capacitors with Ni internal electrodes were performed within the paraelectric phase. We observed two TSC peaks and inferred that one of them was related to the resistance degradation according to the electromigration of oxygen vacancies. Further, we proposed that the two peaks resulted from the relaxation phenomenon of the oxygen vacancies, which migrated under dc electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 9 publications
2
48
0
Order By: Relevance
“…Meanwhile, the activation energy values of peak B are in the range of 0.64-0.76 eV and the average value is 0.71 eV. According to the movement of relaxation peaks and the activation energy value, it can be concluded that the relaxation peak B should be generated by oxygen vacancies (V O ) [16][17][18][19][20][21][22]. By comparing the activation energies of peak A and peak B, it can be concluded that peak A shows the higher value than peak B.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Meanwhile, the activation energy values of peak B are in the range of 0.64-0.76 eV and the average value is 0.71 eV. According to the movement of relaxation peaks and the activation energy value, it can be concluded that the relaxation peak B should be generated by oxygen vacancies (V O ) [16][17][18][19][20][21][22]. By comparing the activation energies of peak A and peak B, it can be concluded that peak A shows the higher value than peak B.…”
Section: Resultsmentioning
confidence: 98%
“…10b that the V O relaxation shows a long relaxation time in the range of 160-930 ls and an increase tendency with TSDC peak density, which is correlated with the migration of the polarized oxygen vacancies in dielectrics. The oxygen vacancies are depleted in the anodic region and piled-up in the cathodic region after polarization [16][17][18][19][20][21][22]. Under the suitable polarization conditions, some oxygen vacancies can migrate across the grain boundaries into adjacent grains.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations